Revealing the Friction Stress of Microalgae in Microfluidic Devices through Mechanofluorochromism - Lorenzo Casimiro; Rémi Métivier; Bruno Le Pioufle; Sakina Bensalem; Clémence Allain (Advanced Materials Interfaces, 2023)
Abstract Polydiacetylenes are deeply investigated for their mechanofluorochromic behavior: the blue, non‐emitting solid phase, obtained by photopolymerization of the diacetylene precursor, is converted to the red, emitting one by a mechanical stimulus. Inspired by the great potentiality of these compounds to act as microscale force probes, the mechanofluorochromism is implemented in microalgae biotechnology. Indeed, mechanical solicitations in a microfluidic chip can weaken the cellular envelope and facilitate the extraction of high‐added value compounds produced by the microalgae. Herewith, a polydiacetylene‐based mechanofluorochromic sensor is reported to be able to detect the stress applied to microalgae in microchannels. A triethoxysilane diacetylene precursor is designed that photopolymerizes in a purple, low‐emissive phase, and is converted to the red, high‐emissive phase upon mechanical stress. Hereafter, a protocol is set up to chemically graft in the microfluidic channels a polydiacetylene layer, and eventually proves that upon compression of Chlamydomonas reinhardtii microalgae in restricted areas, the friction stress is revealed by the mechanofluorochromic response of the polydiacetylene, leading to a marked fluorescence enhancement up to 83%. This prototype of microscale force probes lays the ground for microscale stress detection in microfluidics environments, which can be applied not only to microalgae but also to any mechano‐responsive cellular sample.